(untitled) (Journal of Mathematics Mechanics and Computer Science, 2011)
For the equation of heat conduction in oil in a pipe-line, the inverse heat transfer problem is considered. By the change of the oil temperature at given points during a given time interval, the coefficient of heat exchange with outer medium is determined. This problem is solved using Fourier method.